Paternò–Büchi photochemical [2 + 2] cycloaddition of aromatic carbonyl compounds with 2‐siloxy‐1H‐pyrrole derivatives†. (31st August 2016) - Xue, Jianfei; Abe, Manabu; Takagi, Ryukichi; Abe, Manabu; Sheridan, Robert S.
Abstract : The purpose of this study was to explore regioselectivity and stereoselectivity in the Paternò–Büchi reaction of pyrrole derivatives. Theregioselective formation of a bicyclic oxetane in the Paternò–Büchi reaction of 2‐siloxypyrrole with benzophenone was reported for the first time, and a mechanism involving the distribution of the intermediary triplet diradicals was proposed to account for the regioselectivity of the reaction. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The synthesis of the isolable bicyclic oxetane in the Paternò–Büchi reaction of pyrrole derivatives was reported for the first time, and the synthetic scope and limitation, and the reaction mechanism were discussed in detail.